Caracterização funcional da BaltMTx, uma miotoxina isolada da peçonha de Bothrops alternatus - Pereira, Déborah Fernanda da Cunha (2015)
CHAPTER II: Snake venoms are a complex mixture of organic and inorganic compounds, proteins and peptides such as aminotransferases, acetylcholinesterase, hyaluronidases, L-amino acid oxidase, phospholipase A2, metalloproteases, serine proteases, lectins, disintegrins, and others. Phospholipase A2 directly or indirectly influence the pathophysiological effect on envenomation, as well as their participation in the digestion of the prey. They have several other activities such as hemolytic indirect action, cardiotoxicity, aggregating of platelets, anticoagulant, edema, myotoxic and inflammatory activities. In this work, we describe the functional characterization of BaltMTx, a PLA2 from Bothrops alternatus that inhibits platelet aggregation and present bactericidal effect. The purification of BaltMTx was carried out through three chromatographic steps (ion-exchange on a DEAE-Sephacel column, followed by hydrophobic chromatography on Phenyl–Sepharose and affinity chromatography on HiTrap™ Heparin HP). The protein was purified to homogeneity as judged by its migration profile in SDS–PAGE stained with coomassie blue, and showed a molecular mass of about 15 kDa under reducing conditions and approximately 25 kDa in non-reducing conditions. BaltMTx showed a rather specific inhibitory effect on platelet aggregation induced by epinephrine in human platelet-rich plasma in a dose-dependent manner, whereas it had little or no effect on platelet aggregation induced by collagen or adenosine diphosphate. BaltMTx also showed antibacterial activity against Staphylococcus aureus and Escherichia coli. High concentrations of BatlMTx stimulated the proliferation of Leishmania (Leishmania) infantum and Leishmania (Viania) braziliensis. BaltMTx induced production of inflammatory mediators such as IL-10, IL-12, TNF-α and NO. BaltMTx could be of medical interest as a new tool for the development of novel therapeutic agents for the prevention and treatment of thrombotic disorders as well as bactericidal agent.